Why do we have Purkinje fibers deep in our heart? - Sedmera, D; Gourdie, R G (Physiological research, 2014)
Purkinje fibers were the first discovered component of the cardiac conduction system. Originally described in sheep in 1839 as pale subendocardial cells, they were found to be present, although with different morphology, in all mammalian and avian hearts. Here we review differences in their appearance and extent in different species, summarize the current state of knowledge of their function, and provide an update on markers for these cells. Special emphasis is given to popular model species and human anatomy.
Keywords: biologické hodiny; spřažení excitace a kontrakce; anatomické modely; Purkyňova vlákna; Animals; akční potenciály; lidé; Action Potentials; Models, Anatomic; Models, Cardiovascular; Excitation Contraction Coupling; Humans; Biological Clocks; zvířata; modely kardiovaskulární; Purkinje Fibers